Rich dad poor dad : with updates for today's world--and 9 new study session sections - Kiyosaki, Robert T. (Scottsdale, AZ : Plata Publishing, 2017)
Taking to heart the message that the poor and middle class work for money, but the rich have money work for them, the author lays out a financial philosophy based on the principle that income-generating assets always provide healthier bottom-line results.
20 years... 20/20 hindsight --
Introduction --
Lesson 1: The rich don't work for money --
Lesson 2: Why teach financial literacy? --
Lesson 3: Mind your own business --
Lesson 4: The history of taxes and the power of corporations --
Lesson 5: The rich invent money --
Lesson 6: Work to learn, don't work for money --
Overcoming obstacles --
Getting started --
Still want more? Here are some to do's --
Final thoughts.
ENH
Hye Trade International
Keywords: Finance, Personal; Investments; Rich people; English language